KERJA SAMA PERPUSTAKAAN INSTITUT TEKNOLOGI BANDUNG DENGAN KEDUTAAN AMERIKA SERIKAT DALAM MEMENUHI KEBUTUHAN REKREASI MELALUI AMERICAN CORNER - Prasetya, Ahmad Fauzi; Rachmawati, Tine Silvana (Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2024)
Academic libraray can be an example where this recreational function is less developed, in contrast to other functions seen from the various new service developments that exist in libraries. Limited space for libraries to develop recreational services can be because the directorate/field that oversees the library does not understand the function of the library as a recreation area or there are limited costs. However, these circumstances should not restrict academic library from developing recreational services. One solution that can be done by the library is to cooperate with other parties, such as the ITB library (Bandung Institute of Technology) with the United States (US) embassy in providing American Corner. This research uses qualitative research methods with a descriptive approach. The data collection techniques used are observation, direct interviews, and literature studies. The results of this study show that the US embassy provides various grants in the form of collections, goods, and funding for the needs of the American Corner ITB facility. Facilities available at American Corner include a variety of magazines, classic and latest novels, comfortable chairs and sofas for reading, board games, TVs, iMacs, 3D printers, Arduino, VR headsets, TVs, and DVD players. These facilities and collections are always used by students for their recreational purposes. The ITB library also mentioned that students gave positive feedback about the existing facilities.